2022
DOI: 10.1101/2022.12.21.521413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability of Phenylalanine side chain conformations facilitates promiscuity of Fatty acid binding in Cockroach milk proteins

Abstract: The pacific beetle cockroach, Diploptera punctata, is a viviparous cockroach that produces a milk-like substance to support the growing embryo with a brood sac. The structure of the in vivo grown crystals present in the gut of the embryo showed that the milk-derived crystals are heterogenous and are made of three proteins (called Lili-Mips). Multiple fatty acids could be modeled into the active site, and we hypothesized that each of the three isoforms of the protein bound to a different fatty acid. We previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…S1. After this initial structural relaxation, further change in structure occur more gradually indicating equilibrium sampling in all the four systems including the G NL and NG NL where we removed the lipid substrate, indicating that the structural integrity is maintained even in the absence of ligand that conforms to previous findings 7 . Comparing all the 4 systems we observed that the glycosylated forms (G L and G NL) have relatively larger values of RMSD than the non- glycosylated forms.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…S1. After this initial structural relaxation, further change in structure occur more gradually indicating equilibrium sampling in all the four systems including the G NL and NG NL where we removed the lipid substrate, indicating that the structural integrity is maintained even in the absence of ligand that conforms to previous findings 7 . Comparing all the 4 systems we observed that the glycosylated forms (G L and G NL) have relatively larger values of RMSD than the non- glycosylated forms.…”
Section: Resultssupporting
confidence: 82%
“…At this point we must be cognizant of the fact that such transitions in lipid orientations can take place only if the barrel structure is sufficiently flexible. However former studies have shown that the glycans do not affect the overall pocket volume of Lili-Mip 7 . Hence a subtle re-arrangement of interior residue orientations might facilitate the lipid’s access to the buried residues.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation